The Role of Premorbid Psychiatric History and Current Mood Ratings on Self-Reported Concussion Symptom Severity. (26th July 2019) - Presley, C; Tarkenton, T; Meredith-Duliba, T; Sabo, T; Miller, S; Bell, K; Batjer, H; Cullum, C M
Abstract: Purpose: Psychiatric history is known to be relevant to concussion outcomes, although less is known about the role of such factors or current mood ratings in adolescents. The aim of this study was to assess the role of premorbid psychiatric history (PPH) and current mood ratings (CMR) on overall sports-related concussion (SRC) symptomology and cognitive outcomes in adolescent and young adult athletes. Methods: Participants age 12–25 years (M=14.8) diagnosed with SRC (n=560) were evaluated within 14 days of injury as part of the North Texas Concussion Registry (ConTex) using the Patient Health Questionnaire-8 Items (PHQ-8), General Anxiety Disorder-7 Item Scale (GAD-7), and ImPACT. Subjects were dichotomized into those with (PPH+) and without (PPH-) pre-existing reported psychiatric diagnoses, and CMR groups were determined by normal vs. elevated scores on the GAD-7 and PHQ-8. T-tests were used to compare groups. Results: Significant differences in total symptom severity scores were found between both PPH (p=.01) and CMR (p<.001) groupings. PPH+ (n=27) reported significantly higher symptom scores (M=31.6) than PPH- subjects (n=316, M=20.9). Additionally, those reporting elevated CMR endorsed 2.3x higher symptom severity scores (n=48, M=42.1 vs. n=276, M=18.2). Among ImPACT cognitive scores, only Visual Memory differed between CMR groups (p=.047). Conclusion: Findings suggest that PPH and elevated CMR are associated with greater self-reported symptom severity in adolescent SRC, but have little relationship to cognitive outcomes as assessed by ImPACT. Further research is needed to understand the interaction between PPH, CMR, and SRC recovery across the age spectrum.